Electrochemical growth of self-organised anodic TiO2 nanotubes for better photocatalytic degradation reaction - Lau, K.S.; Lai, C.W.; Lim, Y.S.; Abd Hamid, S.B. (Maney Publishing, 2014)
Self-organised anodic TiO2 nanotubes have been synthesised via electrochemical anodisation of Ti foil. In our present study, addition of 1 vol.-% of distilled water into the electrolyte was to increase the field-assisted oxidation rate for producing highly-ordered TiO2 nanotubes. Interestingly, it could be observed that nanotubes with a length of 1.71 mu m and pore diameter of 76 nm were formed after 20 minutes of oxidation. However, the length of the nanotubes did not grow linearly with anodisation time. This observation infers that fluoride content played a crucial role in controlling the chemical etching and dissolution rate in order to grow highly ordered nanotubes at longer anodisation times. Based on our photocatalytic studies, higher aspect ratio (length to diameter) TiO2 nanotubes exhibited better photocatalytic degradation of methyl orange because of the high active surface area for photon absorption from ultraviolet illumination to promote more 1 electron-hole pairs.